Serbia and Montenegro : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2005)
This Report assesses Observance of Standards and Codes on the Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Serbia and Montenegro. The assessment reveals that the AML/CFT regime of Serbia still lacks some essential components. On the repressive side, there is not a specific provision on the financing of terrorism. It is possible to confiscate the proceeds of crime, but it is not possible to confiscate money intended to finance an act of terrorism.